Analisis dan Perancangan Sistem Informasi Pemesanan Roti Online 'Rotiku' Berbasis Website dengan Model Bisnis B2C untuk Toko Roti Skala Kecil - M. Randam Fihan Sugiarto; Dinar Kurniawan; Vrisco Seno Aji; Amalia Yusrina Lutfiani (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of information technology is driving digital transformation in various sectors, including the food industry. To meet this need, the "Rotiku" website was designed and developed as an online bread ordering solution, especially for small-scale bakeries. This website carries a B2C business model, built using Laravel technology and a MySQL database, and applies a prototyping approach to ensure the system can meet user needs. This website makes it easy for customers to view the product catalog, order bread, and choose digital payment methods such as QRIS, further simplifying transactions. In addition, shop owners and admins are provided with comprehensive features to manage products, monitor orders, and generate real-time sales reports. As part of the system performance evaluation, an analysis was conducted using the PIECES approach, comparing the performance of the website system with the previously used manual method. The analysis results showed significant improvements in several aspects, including system performance, quality of information presented, operational efficiency, and service enhancements. The Rotiku website is expected to improve service quality and customer satisfaction through ease and convenience in ordering, as well as assist shop owners in managing operations more efficiently. With this system, bakeries not only benefit from easier product management and ordering, but also from faster and more accurate sales monitoring. The implementation of the Rotiku website is expected to positively impact the development of small-scale bakeries, improve operational efficiency, and provide a better and more modern shopping experience for customers. This system is an innovative solution that can support bakery business growth and expand market reach digitally. The Rotiku website is expected to improve service quality, operational efficiency, and overall customer satisfaction.